The Effect of Muntingia calabura L. Leaf Extract Administration on Blood Glucose Levels and Sperm Motility and Viability in Streptozotocin-Induced Mice - Pritasari, Ilham Arzy Diana; Hasanah, Uswatun; Harfiani, Erna; Nurcita, Boenga (Al-Kauniyah: Jurnal Biologi, 2026)
Increased reactive oxygen species levels, a result of antioxidant imbalance in diabetic, can affect metabolism and cellular respiration, especially spermatogenesis that affects sperm quality. Muntingia calabura has proven to be effective as an antidiabetic and rich antioxidant through several studies. This study aims to analyse the effectiveness of Muntingia leaf extract on blood sugar levels, sperm motility, and viability in mice induced by streptozotocin. A diabetic animal model was developed with repeated low doses of streptozotocin. The group  was divided into 5 groups, which are the negative control, positive control, and three extract groups (100, 150, 200 mg/kg). Blood sugar tests showed that the positive control group, mice induced with streptozotocin without Muntingia leaf extract, had the highest blood sugar levels. Treatment groups with Muntingia leaf extract had different results, those groups successfully reduced blood sugar levels to normal levels. The highest dose, 200 mg/kg, of Muntingia leaf extract reached 85.9% normal sperm motility and 82.9% sperm viability. The ANOVA test result showed a significant relationship between blood sugar levels with sperm motility and viability in streptozotocin-induced mice after Muntingia leaf extract administration. Muntingia leaf extract has the potential to reduce blood sugar levels in hypergly-cemic conditions and to improve sperm motility and viability.